Cryptographic Algorithm Using Matrix Inversion as Data Protection - Zirra, Peter B.; Wajiga, G.M. (Universiti Utara Malaysia Press, 2011)
This study aimed at providing algorithms to secure sensitive information in store or in transit via unsecure channels from the hands of the Internet criminals by scrambling the sensitive information into a set of linear equations in matrix form and deciphering by solving the systems of the linear equations in conjunction with the principles of the delta encoding scheme, a formula and a lookup alphanumeric position table. The algorithms were tested with samples of real data and the result practically demonstrated how systems of non-linear equations turned into linear equations are indeed of relevance in providing strong and complex encryption and decryption keys to protect sensitive information in store or in transit via unsecure channels. The proposed algorithms ensured that unauthorized users do not have access to sensitive and classified documents stored or transmitted to an intended recipient without a secret key. This means that, there is confidentiality, non-repudiation and integrity of our sensitive and classified information from the hands of unauthorized users on the Internet because of the robustness of the proposed algorithms.